Evaluation Of The Role Of Consumer - Atmosphere Congruence And Social Media Influence On Purchase Intention And Recommendation Intention – Case Of Pizza Hut - Nurlena, Nurlena; Fardiaz, Dedi (International Journal of Multidisciplinary Sciences, 2024)
Due to its growing popularity, social media has become a marketing channel and has been shown to influence consumer purchasing decisions. Furthermore, Consumer will prefer to visit culinary places with an atmosphere of Instagram able concept attractive to create an impression on consumers through visual communication, color, lighting, music, and aroma. Many culinary industries use Instagram to maximize their performance by communicating their products, include Pizza Hut. Changes in people's lifestyles today, which lead to mobile working, have resulted in business people, especially in the culinary field, only sometimes having to promote products or services traditionally but can use social media as a means of promotion. The purposes of this reserach are to know consumer atmosphere congruence influence the consumer's decision on purchase intention and recommendation intention, and to know social media influence the consumer's decision on purchase intention and recommendation intention. Qualitative research method used in this thesis to evaluate the role of consumer atmosphere congruence and social media influence on purchase intention and recommendation intention, specifically for Pizza Hut restaurants. Data from Pizza Hut consumers were collected through both in-depth face-to-face interviews and online survey using questionnaires. The  findigs of this research that by evaluating three different indicators for assessing the consumer atmosphere congruence and social media influence, this study shows that design factors, ambient factors, and social factors, can attract and generate interest in buying visitors. Furthermore, consumers agree that Pizza Hut social media influence which are attractive and trustworthy can attract and generate interest in buying visitors at Pizza Hut. The results of this study are expected to be used by store managers to increase the number of consumer visits to Pizza Hut. It was found that social media marketing has a positive effect on purchase intention which is the basis for researchers to provide information to improve performance for the Pizza Hut restaurant.